Scenario assessments of climatic warming and population mortality in russian cities located in the sub-arctic regions in XXI century - D.A. Shaposhnikov (Analiz Riska Zdorovʹû, 2019)
Climatic changes are the most apparent in the Arctic. Climatic forecasts indicate that warming is continuing on circumpolar territories. There is a vital task to determine attributive fraction of mortality caused by exposure to non-optimal temperatures within the given scenarios. We obtained a dependence of daily mortality on average daily temperatures within a non-linear model with a distributed lag. Daily temperature anomalies that were expected to occur by the middle and the end of the XXI century were calculated as per ensemble calculations of a regional climatic model by Voyekov’s Chief Geophysical Observatory; the calculations were made with applying representative trajectories for greenhouse gases concentrations built by the Intergovernmental Expert group on Climatic Change: RCP4.5 that led to moderate warming, and RCP8.5 that led to the maximum warming. Warming in Russian cities located in the sub-Arctic regions would be accompanied with a general decrease in tem-perature-dependent mortality. A decrease in cold-induced mortality was more than enough to compensate for an increase in heat-induced mortality for all the examined sub-Arctic territories and warming scenarios. Therefore, the ultimate effect turned out to be quite favorable as mortality caused by all the natural reasons among people older than 30 would decrease by 4.5 % in Murmansk (95 % CI 1.1 – 7.9 %; by 3.1 %, in Arkhangelsk (1.1–5.1 %); and in Yakutsk, by 3.6 % (0.3–7.0 %) by 2090–2099 against 1990–1999 within RCP8.5 scenario that involved strong radiation impacts on the climatic system. Expected relative decrease in mortality in Russian Arctic regions could be by several times higher than in the Northern Europe with confidence intervals of obtained assessments being rather similar to each other. These research works complement each other thus indicating that benefits and risks caused by global warming are going to be distributed unevenly.